Building Stability in the Middle East: An Analysis of Political Integration through the GCC and the Arab League - Mustofa, Ahmad Zainal (Middle Eastern Studies Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
This study aims to examine the impact of regional integration policies on interstate relations and political stability in the Middle East. The main focus of the research includes analyzing the influence of these policies on diplomatic cooperation, political stability, and regional security. Additionally, the study will identify the challenges and obstacles hindering the effectiveness of regional integration and propose strategies to enhance integration with a more inclusive and cooperative approach. To elaborate on the discussion, the author uses regionalism theory. The method used is descriptive-analytical. The study concludes that regional integration in the Middle East faces significant challenges, such as dependence on hydrocarbon exports, which limits the development of industry and the private sector in GCC countries. Economic disparities between wealthy countries like Saudi Arabia and Qatar and poorer countries like Yemen are exacerbated by the migration of young professional workers to the GCC. In addition to economic issues, the region also faces insecurity in food, water, and energy. Internal conflicts, cultural identity differences, and political rivalries often hinder the effectiveness of regional cooperation. To achieve better integration, an approach that involves intergovernmental dialogue, inclusive strategies, and the active participation of civil society and the private sector is required.